Relaxation of isolated aorta of the rabbit by picolinic acids. - Asano, M (1977)
1 When the isolated thoracic aorta of the rabbit was contracted with prostaglandin F2alpha, 5-alkylpicolinic acids produced dose-dependent relaxations. 2 Picolinic acid, 2,5-pyridinedicarboxylic acid and 5-acetylpicolinic acid which do not have the 5-alkyl residue failed to relax blood vessels. 3 The vascular relaxation was dependent on the number of carbon atoms in the 5-alkyl compounds. 4 Relaxations which occurred with 5-alkylpicolinic acids were not affected by pretreatment with either propranolol or atropine. 5 It is concluded that the 5-alkyl residue is necessary for the vascular relaxation with 5-alkylpicolinic acid and that it was not produced by stimulation of beta-adrenoceptors or cholinoceptors but rather through an activation of the basic process.